Preoperative percutaneous Onyx embolization of carotid body paragangliomas with balloon test occlusion - Kelblová, Martina; Vaníček, Jiří; Gál, Břetislav; Rottenberg, Jan; Bulik, Martin; Cimflová, Petra; Křivka, Tomáš (Frontiers in Neurology, 2023)
Objectives The study aims to analyze our first experience with direct percutaneous embolization of carotid body tumors (CBTs) using ethylene-vinyl alcohol copolymer (Onyx) along with balloon test occlusion (BTO). Methods A retrospective preliminary single-center study was conducted at the Otorhinolaryngology and Head and Neck Surgery Department and the Medical Imaging Department of the University Teaching Hospital. A consecutive series of three patients with CBTs was treated at the local institution between October 2018 and June 2019. All three patients underwent preoperative percutaneous embolization using ethylene-vinyl alcohol copolymer (Onyx 18) with the addition of BTO. Outcome measures were the percentage of tumor devascularization, intraoperative blood losses, and operation times. BTO was evaluated by clinical neurological examination and neurosonological transcranial Doppler examination of the middle cerebral artery (MCA). Results Devascularization of all three tumors was complete or near complete. All three tumors were surgically extirpated with excellent surgical outcomes. The blood losses were minimal, and the average operation time was 2 h and 8 min. BTO was positive in one patient, which was valuable additional information on carotid branches ligation limitations. The other two patients showed negative BTOs with the result of safety of eventual carotid arteries ligations. Conclusion Preoperative direct percutaneous embolization of CBT with Onyx is a highly effective procedure that significantly facilitates surgery. BTO provides valuable additional information on the most appropriate and safe surgical approach.